2015
DOI: 10.1007/s00590-015-1660-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of the Forgotten Joint Score-12 as a universal patient-reported outcome measure

Abstract: The FJS-12 was correlated with and showed reliability similar to that of the JHEQ and WOMAC. The FJS-12, which is not affected by culture or lifestyle, may be useful in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…Matsumoto et al performed a survey of the relation among FJS-12, JHEQ, and WOMAC after THA [28]. They concluded that the FJS-12 showed a lower mean score than the WOMAC or JHEQ and tended to show greater dispersion and more marked differences among patients [28]. Although there was no statistical difference in the JHEQ score between both groups, patients with LFCN injury reported a lower QOL than those without.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Matsumoto et al performed a survey of the relation among FJS-12, JHEQ, and WOMAC after THA [28]. They concluded that the FJS-12 showed a lower mean score than the WOMAC or JHEQ and tended to show greater dispersion and more marked differences among patients [28]. Although there was no statistical difference in the JHEQ score between both groups, patients with LFCN injury reported a lower QOL than those without.…”
Section: Discussionmentioning
confidence: 89%
“…In other words, any small subjective complaint might affect 'awareness', which explains why a significant difference was observed between those with LFCN injury and those without. Matsumoto et al performed a survey of the relation among FJS-12, JHEQ, and WOMAC after THA [28]. They concluded that the FJS-12 showed a lower mean score than the WOMAC or JHEQ and tended to show greater dispersion and more marked differences among patients [28].…”
Section: Discussionmentioning
confidence: 97%
“…FJS-12 is a questionnaire that focuses on the awareness, instead of the pain of the affected joint. The main characteristic of the FJS-12 that is not observed in other tools is that discrimination among ''good,'' ''very good,'' and ''excellent'' is possible using relatively abstract questions to ask whether patients are aware of their artificial joint during activities of daily living (Matsumoto et al, 2015). Our sample has a moderate score for FJS-12 compared to the literature.…”
Section: Discussionmentioning
confidence: 86%
“…All patients underwent CT scans of the lower limb according to the standardized Perth protocol [12], and detailed measurement of coronal, sagittal, and rotational alignment was performed by a blinded independent assessor (CG, SH). Patient-reported outcomes were assessed using the Oxford Knee Score (OKS, 0-48 worst to best) [33], the reduced WOMAC (0-100 worst to best) score [42], the pain and function components of the Knee Society Score (KSS, 0-100 worst to best) [26], the Forgotten Joint Score (FJS, 0-100 worst to best) [4,31], EuroQol EQ-5D [11], and visual analog scales measuring pain at rest and when mobilizing (0-10 none to worst). Scores were measured preoperatively and at 6, 12, and 24 months postoperatively.…”
Section: Methodsmentioning
confidence: 99%